Indolyne and aryne distortions and nucleophilic regioselectivites. - Cheong, P; Paton, R; Bronner, S; Im, G; Garg, N; Houk, K (2010)
Density functional theory computations reproduce the surprisingly high regioselectivities in nucleophilic additions and cycloadditions to 4,5-indolynes and the low regioselectivities in the reactions of 5,6-indolynes. Transition-state distortion energies control the regioselectivities, activating the 5 and 6 positions over the 4 and 7 positions, leading to high preferences for 5- and 6-substituted products from 4,5- and 6,7-indolynes, respectively. Orbital and electrostatic interactions have only minor effects, producing low regioselectivities in the reactions of 5,6-indolynes. The distortion model predicts high regioselectivities with 6,7-indolynes; these have been verified experimentally. The regioselectivities found with other arynes are explained on the basis of distortion energies that are reflected in reactant geometries.